Development and evaluation of sustainable hydrogel technologies for tissue engineering - Kret, Kayla Danielle (2021)
With an increasingly active and aging population, injury to ligaments and tendons poses a serious issue to the healthcare system. For ruptures of these ligaments and tendons which cannot be treated conservatively, surgical intervention may be required for an adequate return to health. Current reconstruction options require autologous tissue which can prolong the rehabilitation period and cause inadvertent pain at the donation site. While allografts avoid pain at donation site, they may cause foreign body responses and there is a finite availability of allograft tissue. Therefore, a regenerative therapeutic solution is required that can overcome the known issues of current available grafts for ligament and tendon repair. Recent advances within tissue engineering have led to a deeper understanding of the ligament repair process while circumventing the concerns of autografts and allografts. Challenges arise in creating a scaffold that properly assimilates the ligamentization process while simultaneously offering adequate mechanical strength and tissue formation. Further challenges emerge in recreating the natural graded mineralization of the ligament into fibrocartilage and bone found at the enthesis, or bony insertion region, that is necessary for stress dispersal. The overall aim of this research was to develop a hydrogel scaffold made from sustainable biomaterials for use in a ligament tissue engineering application that can withstand physiological loading while influencing a fibroblastic response at the midsubstance and an osteoblastic response at the entheses. A cost-effective approach was taken in this research by incorporating materials that are either routinely used in cell culture or readily available at low cost. The work reported in this thesis describes the development of a chitosan-gelatin hydrogel into a ligament construct, or sinew, consisting of a soft, ligamentous midsubstance and a stiff, bony interface that could be implemented in a tensile loading bioreactor. The thickness of the chitosan-gelatin hydrogel was optimised to promote cell proliferation and production of ligament-like ECM using the NIH-3T3 fibroblast cell line and a primary ovine fibroblast culture. A novel method was developed to fabricate the hydrogel into a detached form that allowed its use in a tensile loading bioreactor system. The method of producing the detached hydrogel scaffolds did not affect the cytocompatibility of the hydrogel but was found to decrease the internal rigidity of the scaffold. The incorporation of calcium phosphate salts into the chitosan-gelatin hydrogel created a composite hydrogel suitable for enthesis engineering that prompted an osteogenic response from the primary fibroblast culture. The responses of the two fibroblast cultures were analysed on the chitosan-gelatin hydrogel and composite hydrogel to determine their suitability as a cell source for ligament tissue engineering applications. Both cultures showed a fibroblastic response on the chitosan-gelatin hydrogel, which would maintain the ligament phenotype in the midsubstance of the scaffold. The 3T3 cell line was vital in the early investigation of the chitosan-gelatin hydrogel, however its response was limited on the composite hydrogel. The primary cell culture demonstrated an osteogenic response on the composite hydrogel. Due to this, it was determined that the primary fibroblast culture was a more suitable cell source for a ligament tissue engineering application. The hydrogel sinews were successfully implemented into a tensile loading bioreactor system capable of applying physiological strain and seeded with the primary fibroblast culture. The effect of the tensile strain on the attached fibroblasts was analysed in comparison with a static culture system. This custom tensile loading bioreactor system was designed as a model for ligament tissue engineering research.